Role of masked coronary heart disease in patients with recent-onset atrial fibrillation and troponin elevations. (June 2015) - Conti, Alberto; Mariannini, Yuri; Canuti, Erica; Cerini, Gabriele; De Bernardis, Niccolò; Gigli, Chiara; Giampieri, Margherita; Viviani, Gabriele; Poggioni, Claudio; Padeletti, Luigi
<x xml:space="preserve">Abstract</x> Background Patients with recent-onset atrial fibrillation (AF) and cardiac troponin I (cTnI) elevations show poor outcomes. Coronary heart disease might be a cause, consequence, or an innocent bystander. Objective The aim of this study was to recognize and treat coronary heart disease to avoid adverse events. Methods Patients with recent-onset AF participated in the study. The exclusion criteria were acute coronary syndrome and severe comorbidities. Patients managed with standard care (group 1, n=1086, years 2010–2011) were compared with patients managed with tailored care inclusive of echocardiography and stress testing when required (group 2, n=1055, years 2012–2013). Endpoint The endpoint was a composite of ischemic vascular events including stroke, acute coronary syndrome, revascularization and cardiovascular death at 6 months of follow-up. Results Of 4008 patients considered, 2141 were enrolled; 183 showed cTnI elevations, 92 in group 1 and 91 in group 2. cTnI elevations, known ischemic heart disease and age were predictors of the endpoint on multivariate analysis. Overall, two versus seven patients (P=0.033) in groups 1 and 2, respectively, underwent revascularization. Eventually, 16 patients in group 1 versus five patients in group 2 reached the endpoint (P=0.019). Patients of group 2 were managed as follow: 35 were admitted, 15 with positive stress testing and 20 with high cTnI values (mean values: 0.64±1.01 ng/ml). Fifty-six patients were discharged with negative stress testing results (n=13) or very low cTnI values (n=43, mean values 0.29±0.30 ng/ml). Conclusion In patients with AF and cTnI elevations, tailored care inclusive of echocardiography and stress testing succeeded in recognizing and treating masked 'critical' coronary heart disease, avoiding adverse events.